ROLE OF ACTIVE KNOWLEDGE SHARING LEARNING METHOD IN IMPROVING ENGLISH LEARNING ACHIEVEMENT FOR STUDENT OF XII-IPA-1 CLASS AT SMA NEGERI 2 MADIUN CITY IN ACADEMIC YEAR 2019/2020 - Warsito Warsito (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
This study aims to: (a) record the improvement of student achievement by applying the Active Knowledge Sharing Learning method; and (b) understand the effect of student learning motivation by applying the Active Knowledge Sharing Learning method. This research used class action research in three rounds. Each round consists of design, activities and observations, reflection, and revision. The onjectt of this research is student of the XII-IPA-1 Class at SMA Negeri 2 Madiun City in Academic Year 2019/2020. The data obtained by using formative test and observation.  Results of the study reveal that the student learning achievement had increased from cycle I to cycle III, are cycle I (69.66%), cycle II (74.53%), and cycle III (83.09%). This study concluded that applying the Active Knowledge Sharing Learning method has a positive effect on the achievement and learning motivation for student.